Kapitały własne w polskim sektorze ubezpieczeń - Jonczyk, Barbara; Nowotarska-Romaniak, Beata; Ogrodnik, Helena (Capital in the Polish Insurance Sector, 2008)
Capital of insurance companies guarantees their stabilization and financial safety. Their value and ways of capital contribution are governed to a great extent by legal regulations. It mainly concerns where the capital comes from, ways of capital contribution and application and the minimal value of subscribed capital. The paper presents the results of an analysis together with the evaluation of the value and structure of capital of insurance companies operating within the Polish insurance sector. The research which was carried out demonstrates that in the analyzed period of time a substantial increase of capital had been noticed. In the beginning, when the Polish insurance sector was being formed, subscribed capitals within the scope of capital played a crucial role. Together with the development of this sector the importance of reserve capital as an element of capital has risen. Foreign investment, to a great extent, had a direct influence on the strengthening of the capital base. However, it should be mentioned that the financial result obtained by insurance sector entities had also an impact on the level of capital as it often (mainly in insurance companies of II sector) reduced the level of these capitals. Nevertheless, changes occurring within the scope of capital in the years 1993-2005 are beneficial. However, it is highly recommended to introduce measures to improve the financial result made by insurance sector companies so that it will not have a negative influence on the level of capital but it should contribute to their increase.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 121-131